Embeddings of the fractional Sobolev spaces on metric-measure spaces. (August 2022) - Górka, Przemysław; Słabuszewski, Artur
Abstract: We study embeddings of fractional Sobolev spaces defined on metric-measure spaces. Various results about continuous and compact embeddings are proven. Many theorems are illustrated by a number of examples.